Mapping coffee base countries in the world: Case studies from three continents (Africa-America-Asia). - Widjaya, Dani; Yanuarti, Rizky (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2024)
The agricultural sector has an important role in the world economy, including the coffee commodity in the plantation subsector. More than 80 countries on the continents of Africa, America and Asia produce coffee and involve more than 100 million people in the process. The growth rate of coffee on these three continents also shows positive values. The aim of this research is to map the countries that are the basis for coffee in the world and look at the prospects for coffee in these countries. The novelty of the research lies in comparing coffee production during the 2017-2022 period in coffee producing countries on three continents, namely Africa, America and Asia. The analysis used to achieve research objectives is Location Quotient (LQ), Dynamic Location Quotient (DLQ) analysis and a combination of both. The research results show that there are 28% of countries on the African continent that have LQ values ​​> 1, 31% on the American continent and 16% on the Asian continent. The DLQ value which shows the prospects for coffee commodities in the future can be seen that on the African continent there are 10 countries that have a DLQ value > 1, while on the American continent there are 13 countries and on the Asian continent there are 9 countries. The American continent has more countries in the Mainstay category (39%), compared to other continents, this indicates that the prospects for coffee commodities on the American continent are quite good in the future.